An Analysis Of The Acceptance Of The Mytens Application As A Government Service Platform By Internal Users Across All Telkom Regional Offices In Indonesia: An Intention To Use Study Based On The Utaut2 Model - Athilayusa, Avania; Apsari Sugiat, Maria (Publisher Cv. Inara, 2025)
Digital transformation has become a key agenda in enhancing industrial competitiveness in Indonesia, as reflected in the Making Indonesia 4.0 roadmap. PT Telkom Indonesia supports this agenda through the launch of the MyTEnS application, designed to assist in operational management within the company, particularly in the Telkom Regional environment across Indonesia. Although it has been implemented, the adoption of this technology still faces challenges, especially in terms of system quality perception and user trust in the application. This study aims to analyze the factors influencing behavioral intention in the use of the MyTEnS application by internal users, specifically Account Managers and Manager Governmenet Services in TREG Nasional. The study adopts a quantitative approach with a modified Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework. The independent variables analyzed include performance expectancy, effort expectancy, social influence, facilitating conditions, price value, habit, and trust. Additionally, two moderating variables, age and gender, were added to examine the influence of the main variables on the intention to use. Data were collected through a survey of 384 MyTEnS users across TREG Indonesia, and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS v3.2.9 software. The results show that performance expectancy, effort expectancy, social influence, facilitating conditions, habit, and trust positively and significantly influence behavioral intention to use the MyTEnS application. Additionally, moderating factors such as age and gender were found to moderate the relationship between several construct variables and behavioral intention. The findings of this study are expected to contribute theoretically to the field of technology adoption and provide practical recommendations for PT Telkom Indonesia in enhancing the adoption and internal use of digital applications, with a focus on improving ease of use, user trust, and better technical support.